2021
DOI: 10.1002/ncp.10737
|View full text |Cite
|
Sign up to set email alerts
|

The use of nutrition support near the end of life for hospitalized patients with advanced cancer at a reference center: Two realities

Abstract: Objective: To assess the frequency and factors associated of the provision of nutrition support (NS) in the last 30 days of life in patients with advanced cancer in the palliative or non-palliative setting.Methods: Retrospective cohort study in palliative and non-palliative care units at a specialized cancer center for oncology in Brazil. The use of oral nutrition supplements (ONS) and enteral (EN) and parenteral (PN) nutrition in the 30 days before death were assessed. Results:The 239 patients included were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In such cases, individual patient assessment and multiprofessional discussion are recommended to ensure conduct that benefits the patient’s life and does not cause harm. Wiegert et al 67 compared the use of nutritional interventions in patients with incurable cancer in palliative care and in non-palliative care and observed that the prevalence of EN and PN was similar in both settings, but that their use decreased significantly with the approach of death in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, individual patient assessment and multiprofessional discussion are recommended to ensure conduct that benefits the patient’s life and does not cause harm. Wiegert et al 67 compared the use of nutritional interventions in patients with incurable cancer in palliative care and in non-palliative care and observed that the prevalence of EN and PN was similar in both settings, but that their use decreased significantly with the approach of death in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the primary research paper reported that when comparing the PNH group to the total 1453 patient group, those who received hydration only was 24.8% (n ¼ 360), and those parenteral nutrition 9.6% (n ¼ 139) [5]. An observational retrospective cohort study conducted in Brazil showed that the frequency of use of oral nutrition supplements, ETF, and parenteral nutrition in the last 30 days of life was lower in palliative than in non-palliative care settings [16]. These findings suggest that palliative care physicians withhold/withdraw parenteral nutrition and also that many palliative care units do not have the expertise to provide parenteral nutrition as readily as parenteral hydration.…”
Section: Discussionmentioning
confidence: 99%
“…The findings obtained also indicated the superiority of enteral nutrition (oral intake and ETF) over PNH; however, only 7.0% of all patients had head and neck cancer or esophageal cancer [17]. An observational retrospective cohort study using data from the last 30 days of life of patients with advanced cancer in Brazil reported that the use of ANH was associated with head and neck cancer in a non-palliative care hospital and palliative care unit [18].…”
Section: Introductionmentioning
confidence: 88%